Graham_et_al_Biology_Letters_Supplementary_Material_TableS5_and_FigureS2_20221206 from Directional hydrophone clusters reveal evasive responses of small cetaceans to disturbance during construction at offshore windfarms - I. M. Graham; D. Gillespie; K. C. Gkikopoulou; G. D. Hastie; P. M. Thompson (2023)
Table S5: The number of seconds and encounters with porpoise detections on hydrophone clusters during the deployment of mitigation measures and baseline periods used to examine directionality of porpoise movements. The distribution of differences in bearings was tested using Rayleigh Tests, initially for uniformity, and then for uniformity against a unimodal alternative with a specified mean direction of 0°. Figure S2: Harbour porpoise movements relative to the sound source per second and per encounter during baseline periods, ADD mitigation and piling soft start.